2012
DOI: 10.1097/rct.0b013e318241e585
|View full text |Cite
|
Sign up to set email alerts
|

Shall We Report Cardiomegaly at Routine Computed Tomography of the Chest?

Abstract: In patients with cancer undergoing routine ECHO, the cardiothoracic ratio at routine CT scans was highly correlated with that at CXR. Preliminary estimates in this small study indicate a low likelihood of LVH when the CTR is less than 0.49.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…In both cases, linear measurements were taken in an adapted way according to the method of Ungerleider and Gubner [6] as described in several previous CT studies [10][11][12]. All measurements were performed on axial slices using the workstation caliper tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, linear measurements were taken in an adapted way according to the method of Ungerleider and Gubner [6] as described in several previous CT studies [10][11][12]. All measurements were performed on axial slices using the workstation caliper tool.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed and adapted the CTR approach to computed tomography (CT) and these measures have been shown to correlate highly with those from CXR [10][11][12]. Despite this, there continue to be differing opinions regarding the clinical reliability and usefulness of the CTR in cross sectional imaging [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Goddard classification was also used to evaluate severity of pulmonary emphysema 45 . CT-based cardiothoracic ratio (CT-CTR) was measured as previously described 46 because CT-CTR was highly concordant to CTR on chest X-ray.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have also shown that CTR can be applied to computed tomography (CT) and therefore post-mortem CT (PMCT) [1,2]. However, this has not been done with ventilated postmortem computed tomography (VPMCT) [8], which can be used to replicate the inspiratory breath-hold chest radiograph that is normally used for CTR.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiothoracic ratio (CTR) is used clinically to assess heart size, as an increased heart size has been associated with risk of cardiovascular disease [1,2]. The use of the CTR was first described using plain-film x-ray in 1919 by Danzer [3].…”
Section: Introductionmentioning
confidence: 99%